Wajib Belajar Perfektif UU. No. 20 Tahun 2003 - Hidayah, Risqy; Siregar, Khoiruddin Manahan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is motivated by the fact that there are still many children who do not continue their education in high school, some of them drop out of school because of the lack of family economy and children's interest in learning who follow their friends. The formulation of the problem in this research is how is the implementation of Law Number 20 of 2003 concerning Compulsory High School Education, what hinders public awareness of the importance of compulsory high school education. The purpose of this study is to find out how the Law Number 20 of 2003 concerning Compulsory High School Education is, and to find out what factors hinder the compulsory education program for school-age children. This study uses descriptive qualitative methods, namely research that is directed to describe the symptoms or events that occur in fact. Informants in this study were children aged 16-18 years as many as 20 people, parents as many as 15 people who were in Gunung Tua Village, Panyabungan District, Mandailing Natal Regency. The data collection techniques used in this study were observation and interviews. The results of the study stated that: the implementation of Law Number 20 of 2003 concerning Compulsory High School Education has not gone as expected, some children have followed the compulsory education program and some have not continued their education. Whereas this law was formed in order to improve the intelligence and ability of children in the nation and state. However, this law has not been able to improve the quality of children's education in Gunung Tua Village. What hinders public awareness of the importance of compulsory education is the lack of attention from parents to their children in the field of education, lack of public knowledge about existing education rules, and the lack of family economy in financing their children's education.